A területfejlesztés folyamatának logisztikai elemei - Bajor, Tibor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The basic rules of the logistique are adaptable as in developing affairs, as in all affairs, realised in a purposive, organised way in the society. Administrative activities and polity are built by a logic system and realised in the frame of the society. Important, the results of the developing policy can not differ much from the needs of its environment, otherwise the adaptation of the development will be pending, and however, the result will have a backlash. That's why we have to aspire to the balance between the developing mind and environmental needs.